The Production of Nickel Carbonate Spheroids from Dilute Solutions in a Pellet Reactor - G. Van Weert (The Minerals, Metals and Materials Society, 1993)
The pellet reactor was developed approximately 20 years ago in the Netherlands for softening drinking water. Since then, some 35 plants have been built, ranging in capacity up to 8500 m3/h. Applications now also include removal of phosphates and fluorides and the production of metal carbonates and sulphides from waste streams. The pellet reactor consists of a fluidized bed, wherein the process solution is thoroughly mixed with the precipitation reagent at special inlet nozzles to give over-saturation of the compound to be precipitated. In water softening applications, the compound is CaCO,. In the case of nickel or other metal waste streams, Na2CO3 solution is added in sufficient amounts to precipitate metal (hydroxy) carbonate on the fluid bed particles. These grow typically to dense spheroids, which are removed when they reach 0.8 to 1.0 mm diameter. These spheroids are easily dewatered, free flowing and low dusting. The latter property is becoming an attractive advantage in connection with new plant hygiene regulations. The operation of a 60 cm diameter pellet reactor on nickel containing plating waste is described and the properties of the produced nickel carbonate spheroids are discussed.